From Computer Aided Chinese Learning to Intelligent Chinese International Education - Li Cemei; Mohd Nazri Abdul Rahman; Ghozali Rusyid Affandi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This article explores the evolution of Computer-Aided Instruction (CAI) in teaching Chinese as a foreign language, from early mainframe systems to the current integration of AI-powered tools. While CAI has improved language learning through multimedia and interactive platforms, challenges remain in effectively integrating cultural context and language complexities like tones and characters. The article discusses how AI-driven systems offer personalized learning experiences, real-time feedback, and the potential to enhance both language proficiency and intercultural understanding. It concludes by highlighting the role of intelligent education in the global spread of Chinese language and the need for further research to optimize CAI technologies for better learning outcomes.